U.S. economic policy toward Africa - Herbst, Jeffrey Ira 1961- (Council on Foreign Relations Books, 1992)
A summary of American aid policy toward Africa since the Kennedy administration, a comparison of U.S. policies and those of multilateral organizations, and a proposal for the best way to help Africans address their continent's economic plight.